Affective lability in parents with schizophrenia or bipolar disorder and their co-parents - The Danish High Risk and Resilience Study VIA 7. (March 2023) - Steffensen, Nanna Lawaetz; Hemager, Nicoline; Bundgaard, Anette Faurskov; Gantriis, Ditte Lou; Burton, Birgitte Klee; Ellersgaard, Ditte; Carlsen, Anders Helles; Bliksted, Vibeke; Plessen, Kerstin J.; Jepsen, Jens Richardt Møllegaard; Nordentoft, Merete; Thorup, Anne A.E.; et al.
Highlights: Parents with schizophrenia or bipolar disorder have elevated affective lability. Affective lability is equally high in schizophrenia and bipolar disorder. Co-parents to parents with schizophrenia have elevated affective lability. Abstract: In bipolar disorder, dysregulation of affect is a core feature while knowledge on affective lability in schizophrenia is sparse. Research on affective lability in partners to individuals with schizophrenia or bipolar disorder is also lacking. The objective of this study was to investigate affective lability in parents with schizophrenia or bipolar disorder, and their co-parents without these disorders. The Danish High Risk and Resilience Study – VIA 7 is a population-based cohort study. This study focuses on parents diagnosed with schizophrenia ( n  = 148), their co-parents ( n  = 157), parents with bipolar disorder ( n  = 98), their co-parents ( n  = 89) and control parents ( n  = 359). The Affective Lability Scale – short form (ALS-SF) was used to measure affective lability. We found significantly higher levels of affective lability in parents with schizophrenia and bipolar disorder compared with controls, but no significant differences between bipolar disorder and schizophrenia. Co-parents to parents with schizophrenia had significantly higher levels of affective lability compared to controls. Our results add to the existing knowledge concerning underlying transdiagnostic factors and nonrandom mating in schizophrenia and bipolar disorder and highlight the need for studies of parental affective lability as a potential risk factor for offspring in families with parental schizophrenia or bipolar disorder.